Glimmers in the Cosmic Dawn: A Census of the Youngest Supermassive Black Holes by Photometric Variability * * This research is based on observations made with the NASA/ESA Hubble Space Telescope obtained from the Space Telescope Science Institute, which is operated by the Association of Universities for Research in Astronomy, Inc., under NASA contract NAS 526555. These observations are associated with programs 11563, 12498, and 17073 - Hayes, MJ; Tan, JC; Ellis, RS; Young, AR; Cammelli, V; Singh, J; Runnholm, A; Saxena, A; Lunnan, R; Keller, BW; Monaco, P; Laporte, N; et al. (American Astronomical Society, 2024)
We report the first results from a deep near-infrared campaign with the Hubble Space Telescope to obtain late-epoch images of the Hubble Ultra Deep Field, 10–15 yr after the first epoch data were obtained. The main objectives are to search for faint active galactic nuclei (AGN) at high redshifts by virtue of their photometric variability and measure (or constrain) the comoving number density of supermassive black holes (SMBHs), n SMBH, at early times. In this Letter, we present an overview of the program and preliminary results concerning eight objects. Three variables are supernovae, two of which are apparently hostless with indeterminable redshifts, although one has previously been recorded as a z ≈ 6 object precisely because of its transient nature. Two further objects are clear AGN at z = 2.0 and 3.2, based on morphology and/or infrared spectroscopy from JWST. Three variable targets are identified at z = 6–7 that are also likely AGN candidates. These sources provide a first measure of n SMBH in the reionization epoch by photometric variability, which places a firm lower limit of 3 × 10−4 cMpc−3. After accounting for variability and luminosity incompleteness, we estimate n SMBH ≳ 8 × 10−3 cMpc−3, which is the largest value so far reported at these redshifts. This SMBH abundance is also strikingly similar to estimates of n SMBH in the local Universe. We discuss how these results test various theories for SMBH formation.